Modelling and simulation of the expansion of a shape memory polymer stent. Issue 8 (7th October 2019) - Liu, Ruoxuan; Mcginty, Sean; Cui, Fangsen; Luo, Xiaoyu; Liu, Zishun
Abstract : Purpose: The purpose of this paper is to demonstrate the feasibility of using shape memory polymer (SMP) for developing vascular stent. In particular, the expansion performance is analyzed through extensive modeling and simulation. Design/methodology/approach: Firstly, the authors construct the model geometry and propose a constitutive model to describe the deformation of the stent due to the expansion process. The authors then simulate the expansion process under varying conditions, including different heating rates and recovery temperatures. Finally, the authors analyze the radial strength of the SMP stent. Findings: A less invasive and stable expansion performance of the SMP stent is confirmed by the simulation method. A fitting function of the expansion process is proposed based on the characteristics of the SMP. Research limitations/implications: The effects of dynamic blood flow on the SMP stent is ignored. A fluid-structure interaction analysis may need to be considered to give a more accurate description of the behaviour of the SMP stent. Practical implications: The findings will provide guidance for the rational design and application of SMP stents. Social implications: The work will provide guidance for the new generation stent design. Originality/value: This is the first time that the expansion performance of a SMP stent has been analyzed both qualitatively and quantitatively through modelling and simulation.